Students’ Perception to the Use of Indirect Corrective Feedback in Writing Recount Text - Endah Anisa Rahma; Siti Sarah Fitriani; Rina Syafitri (IJELR: International Journal of Education, Language, and Religion, 2020)
Providing written corrective feedback is a necessity to help language learner improve accuracy. This research aims to seek out students’ response toward the use of Indirect Corrective Feedback to reduce error on students’ recount text. Tenth graders of SMAN 1 Meulaboh were the sample of this study and observed during the correction. Data from the close-ended questionnaire was analyzed qualitatively andwere calculated using percentage system. The result showed that most students agreed about the implementation of Indirect Corrective Feedback and they believe that this error correction strategy helps them to reduce errors in writing recount text. The result confirm that the students responded positively toward the use of Indirect Corrective Feedback.